Hole localization energy of 1.18 eV in GaSb quantum dots embedded in GaP (Phys. Status Solidi B 10/2016). Issue 10 (7th October 2016) - Bonato, Leo; Arikan, Ismail Firat; Desplanque, Ludovic; Coinon, Christophe; Wallart, Xavier; Wang, Yi; Ruterana, Pierre; Bimberg, Dieter
Abstract : Moore's law, being essentially based on the downscaling of device sizes, is bound to expire soon because of the importance of quantum effects at the nanometre scale. A novel memory architecture, fast and non‐volatile at the same time, is needed to merge the functionalities of DRAM and Flash, thereby radically revolutionizing complex computer architectures and driving energy consumption down. The QD‐Flash is a prototype of such a novel type of memory. It employs III–V semiconductors combined into heterostructures with extreme band gap discontinuities, self‐organised quantum dots and a two‐dimensional hole gas to create the "ultimate memory". QD‐Flash memories recently demonstrated write times in the range of DRAM, storage times of a few seconds at room temperature and erase times much shorter than conventional Flash. In this issue, Bonato et al. (pp. 1877–1881 ) study the storage time of holes in GaSb quantum dots embedded in GaP. They find a storage time as long as 3.9 days at room temperature, marking an improvement of three orders of magnitude from the previous record figure and bringing QDFlash closer to the goal of non‐volatility.